Evaluation of Proximity Switch for Exhaust Fan Interlock System on Pellet Dryer at PT Chandra Asri Pacific Tbk - Felycia, Felycia; Sativa, Oryza; Hartono, Hartono; Nugraha, Adi; Sriwijaya, Sayid Bahri (Universitas Sultan Ageng Tirtayasa, 2025)
Guaranteeing the proficient execution of pellet dryers within the petrochemical segment requests a reliable security and control framework. This inquire about investigates the utilize of an interlock framework utilizing nearness switches on the debilitate fan of a pellet dryer at PT Chandra Asri Pacific Tbk. Vicinity switches serve a crucial function in recognizing inconsistencies within the dryer's rotational speed, subsequently making a difference keep up operational parameters. The framework utilizes an inductive nearness switch to track the revolution of metallic components inside the dryer, transmitting parallel inputs to a recurrence converter. These inputs are changed into real-time information on rotational speed, which are fundamental for activating the interlock reaction in case of variations from the norm. The interlock setup, which is associated to key generation units such as the soften pump and blender, plays a preventive part against chain-reaction disappointments. The comes about appear a steady operational speed extending from 465.7 to 467.5 RPM—well over the least limit of 250 RPM—highlighting the system's unwavering quality. This setup minimizes startling shutdowns and diminishes hardware wear, in this manner boosting both security and operational efficiency.